Biomulch Treatment Effects on Weed Control and Soil Properties in Cassava Plantation - Suwitono, Bayu; Chozin, Muhamad Achmad; Guntoro, Dwi; Suwarto, Suwarto (Department of Agronomy and Horticulture, IPB University, 2023)
Legume Cover Crop (LCC) are plants grown as live mulch so that it is beneficial to the agro-ecosystem and can be included in cropping systems to regulate soil fertility and suppress weed growth. This study aims to determine the benefits of using Arachis pintoi as biomulch applied at different times on weed composition and soil fertility. The experiment was carried out at the Teaching farm of IPB, Jonggol, West Java, Indonesia; the soil type is Ultisol. This study used two factors and was designed in a factorial randomized block design. The first factor was four accessions of cassava “Ketan Malang”, “Genjah Bayam”, “IR Jonggol”, and “Manggu”; the second factor is the time of the biomulch planting: 4, 8, and 12 weeks before planting the cassava, at cassava planting, and without biomulch + manual weeding as the control. Weed vegetation was analyzed before land preparation and before cassava harvest. The physical and chemical properties of the soil were analyzed before and after the biomulch treatment. Our study demonstrated that Melastoma malabathricum, Tetracera indica, Oxalis barrelieri, Mimosa invisa, Ottochloa nodosa, Ipomoea sp and Cyperus sp. are the dominant weeds in the cassava plantation. Biomulch planted four and eight weeks before cassava was able to reduce weed dry weight. All biomulch treatments were able to improve soil density and total pore space. Soil with biomulch planted eight weeks before cassava planting had the highest C-organic (7.59%) and total nitrogen (0.41%).